Muhammad Arsad Nasution - Muhammad Arsad Nasution (Yurisprudentia: Jurnal Hukum Ekonomi, 2015)
From the description above shows that the pattern istinbath Shahrur highest law in determining the law is rationally based on the benefit of objective conditions of social changes that occur in society. Therefore Shahrur assume that the Koran is just qath'i in wurudnya but overall dhalalah is zhanniyah. Qur'an according to him  be interpreted in accordance with the change of the times and the realities of social events. Sunnah also positioned as a pilot ijtihad against the Koran